AN EMPIRICAL STUDY ON THE IMPACT POVERTY ELEVATION OF PROGRAM - SUPRIYA (International Journal of Multidisciplinary Research and Studies, 2020)
A solid foundation for a stable society may be built with the help of a media that is free, independent, and robust. Democracy, freedom, politics, the economy, and international relations all need a potent tool for communication, and it has been shown that the media plays an important role in resolving local, regional, and global concerns and bringing about the necessary reforms. The study investigates the problem of a split between the elite and the masses that exists in the majority of Indian society. The goal of this undertaking is to investigate the past of this division in order to comprehend both the cause and the impact of the phenomena being studied. In addition, while speaking about the elites and the people, "IN RECENT times, the idea of elite has been evoked often in debating the challenges and chances of development in third world nations."